PKM Kelompok Guru Guru Pada PAUD Tentang Pengenalan Vitamin Pada Buah - Buahan Berbasis Android - Agus Darmawan; Syamsiah Syamsiah; Halimatussa'diah Halimatussa'diah (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2023)
In this millennial era, technological developments are developing rapidly, including Android-based smartphone technology. Where almost all of the world of education uses Android-based smartphone technology. The Early Childhood Education participates in using Android technology as a learning medium. Where conventional learning media is still not optimal, so learning media with Android technology is needed so that it can be maximized in delivery. because smartphone technology is needed as a learning medium, our team of lecturers plans to introduce learning media about the introduction of vitamins to android-based fruits as information for children so that they like fruits. It is hoped that with learning media the socialization of early childhood teachers will become more interactive, we are in accordance with the agreement with PAUD teachers. The learning media application for the introduction of vitamins in fruits is made using the waterfall method and assisted by the Android programming language. The output to be achieved from this community service activity is a prototype in the form of an introduction module for vitamins in fruits in the form of learning media in early childhood education. With this module, it is hoped that it can assist teachers in utilizing learning media to improve students' abilities to absorb the material provided by the teacher